In the Flow of Life: Capturing Affective Socializing Dynamics Using a Wearable Sensor and Intensive Daily Diaries. (December 2021) - Zhang, Amy; Goosby, Bridget; Cheadle, Jacob E.
Interpersonal socializing is important to many sociological outcomes, but assessing the affective dynamics within interactional contexts is extremely challenging methodologically. As a first step toward capturing socializing and affective outcomes concurrently, this pilot study ( n = 118) combines intensive daily surveys with a wearable sensor that tracked affective arousal. This approach allowed the operationalization of affect along its two primary dimensions, valence and arousal, which were then linked to periods socializing with a romantic partner, a best friend, and/or a group of friends. Although socializing predicted positive and negative affective valence concurrently in time, only socializing with groups of friends consistently predicted increased affective arousal. Findings for romantic partners and/or socializing with a close friend suggest that low arousal "downtime" with close intimates may also provide important social functions. This work demonstrates a new biosignaling approach to affective dynamics broadly relevant to emotion-related sociological research.